The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1038/hdy.2014.81
|View full text |Cite
|
Sign up to set email alerts
|

Genome data from a sixteenth century pig illuminate modern breed relationships

Abstract: Ancient DNA (aDNA) provides direct evidence of historical events that have modeled the genome of modern individuals. In livestock, resolving the differences between the effects of initial domestication and of subsequent modern breeding is not straight forward without aDNA data. Here, we have obtained shotgun genome sequence data from a sixteenth century pig from Northeastern Spain (Montsoriu castle), the ancient pig was obtained from an extremely well-preserved and diverse assemblage. In addition, we provide t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 46 publications
(71 reference statements)
4
43
0
1
Order By: Relevance
“…Moreover, Figure 1a indicates that neither Spanish Iberian nor Hungarian Mangalica have been crossed with Chinese pigs, as they cluster tightly with European wild boars. Although the absence of any Asian signature had already been conclusively shown in Iberian pigs (Ramírez et al, 2014), the evidence in Mangalica was much more limited (Molnár et al, 2013), but is conclusively shown in these data.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…Moreover, Figure 1a indicates that neither Spanish Iberian nor Hungarian Mangalica have been crossed with Chinese pigs, as they cluster tightly with European wild boars. Although the absence of any Asian signature had already been conclusively shown in Iberian pigs (Ramírez et al, 2014), the evidence in Mangalica was much more limited (Molnár et al, 2013), but is conclusively shown in these data.…”
Section: Resultsmentioning
confidence: 67%
“…Further, rather than being an abrupt change, domestication plausibly involved gradual discontinuities in gene flow between the domestic and the wild populations . This gene interchange, even if small, has continued to the present day in some cases like Mediterranean pigs (Ramírez et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have estimated the genetic diversity of pig breeds worldwide (Faubel et al, 2004; Ramírez et al, 2014;Revidatti et al, 2014). Among those studies, specific results have been published based on the same set of breeds and microsatellites assessed here, reporting the genetic relationships among Iberian Peninsula pig breeds and Criollo pig breeds (Revidatti et al, 2014).…”
Section: Introductionmentioning
confidence: 92%
“…We expect that similar investigations will also largely advance our understanding of domestication processes when applied to other domestic animals. This work has already started in cattle (Edwards et al 2007;Bollongino et al 2008;Orlando 2015;Park et al 2015;Scheu et al 2015), dogs (Ollivier et al 2013;Thalmann et al 2013), swine (Edwards et al 2007;Meiri et al 2013;Ottoni et al 2013;Frantz et al 2015;Ramírez et al 2015), and chickens (Flink et al 2014).…”
Section: Discussionmentioning
confidence: 99%